Neurofibromatosis type 1 associated to cognition deficit, hydrocephaly, bone dysplasia and elephantiasis - Ramírez, Julio (2009)
We report the case of a 31 year-old male from Cajamarca, Peru, with cognitive problems since childhood, who at 12 year-old developed increased volume and deformation of his right lower limb and to a lesser extent of his left, associated to massive skin folding, growth of subcutaneous nodules, elephantine look due to nerve cords formation in thigh and leg, pain and functional walking limitation. Concomitantly generalized skin café au lait spots, subcutaneous nodules, and Lisch nodules in both irides. Magnetic resonance and contrast TAC revealed abundant uniform plexiform nodules in abdomino-pelvic cavity forming masses and cords that continued throughout his thigh as lumps and cords. In addition, the patient presented bone dysplasia (thinning of femur and tibia cortex, pseudoarthrosis, new left cotyle formation). Contrast magnetic resonance showed triventricular normotensive hydrocephalus.